2022
DOI: 10.1200/cci.21.00141
|View full text |Cite|
|
Sign up to set email alerts
|

HealthTree Cure Hub: A Patient-Derived, Patient-Driven Clinical Cancer Information Platform Used to Overcome Hurdles and Accelerate Research in Multiple Myeloma

Abstract: PURPOSE The study of rare diseases, such as multiple myeloma (MM), often experiences unique research hurdles that can delay or prevent lifesaving discoveries. HealthTree Cure Hub is a first-in-class software program designed to overcome these potential research hurdles. METHODS We assessed whether HealthTree Cure Hub improved four commonly experienced research hurdles such as (1) small numbers of patient accrual to clinical trials and research studies, (2) shallow and isolated data sets, (3) high costs to answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For the current study, the following questionnaires were posted on the HealthTree® Cure Hub website (14) between December 2019 and April 2022: visual analog scale for pain; European Organisation for Research and Treatment of Cancer, Quality of Life, Cancer-Related Fatigue Questionnaire (EORTC QLQ-FA12); National Comprehensive Cancer Network (NCCN) Distress Thermometer; and a Basic Assessment of Physical Activity (BAPA) questionnaire, which was developed by the authors specifically to study PA in MM patients. In addition to study-specific questionnaires, the HealthTree® Cure Hub is used to collect self-reported data on an individual's demographics, laboratory values, treatment histories, and other health-related information (15). The study was promoted through email, social media, and community events.…”
Section: Methodsmentioning
confidence: 99%
“…For the current study, the following questionnaires were posted on the HealthTree® Cure Hub website (14) between December 2019 and April 2022: visual analog scale for pain; European Organisation for Research and Treatment of Cancer, Quality of Life, Cancer-Related Fatigue Questionnaire (EORTC QLQ-FA12); National Comprehensive Cancer Network (NCCN) Distress Thermometer; and a Basic Assessment of Physical Activity (BAPA) questionnaire, which was developed by the authors specifically to study PA in MM patients. In addition to study-specific questionnaires, the HealthTree® Cure Hub is used to collect self-reported data on an individual's demographics, laboratory values, treatment histories, and other health-related information (15). The study was promoted through email, social media, and community events.…”
Section: Methodsmentioning
confidence: 99%